ACTIVITIES AND CHARACTERISTICS OF NATIONAL LEADERS WHO ACTED IN THE TURKESTAN ASSR - Bakhodirov Ikhtiyor Bakhodir ugli (Bright Mind Publishing, 2025)
The article provides information on the establishment of Soviet power in Turkestan, the essence of the Soviet system of governance, national leadership personnel who worked in the Council of People's Commissars of Turkestan, and their activities in the regional administration system. In it, based on archival and important sources, the political activities of national leaders in the interests of Turkestan are highlighted. The article notes the specifics of the work activities of national leadership personnel, the ideas they put forward, the goals they set for themselves, and the practical processes for achieving these goals.
Keywords: Council of Commissars, Soviet, Federation, Executive Committee, Bolshevik, National Liberation Movement.